Study on Separation Axioms via Graph Theory - Jasim, Taha H.; Awad, Aiad I. (New Insights into Physical Science Vol. 12, 2021)
A new concept called topological graph and via this concept introduces a new class of separation axioms via the concepts of graph (G-T0, G-T1, G-T2, G-T3, and G-T4), many relations among them were studied and investigated some characterization of these concepts. At last give an application for them.